2019
DOI: 10.1111/cid.12759
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on ultra‐wide diameter dental implants for immediate molar replacement

Abstract: Background Although immediate implant placement for single rooted teeth is well documented, the prognosis of ultra‐wide implants in molar sockets lacks data. Purpose To evaluate the outcome of ultra‐wide implants, immediately placed in molar sockets. Materials and Methods Patients treated with immediate ultra‐wide diameter implants that have been in function for at least 40 months, were invited for a clinical evaluation. A radiograph was taken to measure marginal bone loss. Probing depths as well as plaque and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…However, enough primary stability in molar post-extraction sites is often difficult to achieve. Ultra-wide or wide diameter implant increases the engagement and contact area with the inter-radicular septum and socket walls, and therefore, is frequently used in post-extraction molar sites to overcome the lack of primary stability [ 5 , 16 18 ]. Nonetheless, the long-term prognosis of an ultra-wide diameter implant remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, enough primary stability in molar post-extraction sites is often difficult to achieve. Ultra-wide or wide diameter implant increases the engagement and contact area with the inter-radicular septum and socket walls, and therefore, is frequently used in post-extraction molar sites to overcome the lack of primary stability [ 5 , 16 18 ]. Nonetheless, the long-term prognosis of an ultra-wide diameter implant remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate implant placement in molar extraction sites has been reported to be a valid treatment approach with high survival and success rates [ 2 4 ]. It has given several clinical benefits, such as reduced surgical procedure, ideal implant positioning, and higher patient satisfaction [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specific inclusion criteria would be beneficial for restorative follow‐up. The clinical protocol used in this clinical series correlated well with the guidelines that Hattingh et al 21–25 made regarding ultrawide diameter implant placement.…”
Section: Discussionmentioning
confidence: 66%
“…This posed a significant challenge in our study as it is not possible to match diseased areas with different disease categories, but to overcome this limitation, so to maximize host tissue standardization as much as possible, samples were taken from the same individual's teeth or implants belonging to the same disease group (17). Also; In our study, systemic healthy non-smoking of all participants can be shown as a limitation because it has been reported in the studies that smoking affects mediators, mainly involved in the inflammatory process (33). Similarly, it changes the inflammatory response in diseases such as diabetes mellitus (8).…”
Section: Discussionmentioning
confidence: 99%